Presence of IgG antibodies against reproductive infections in breeding bulls of Magdalena Medio, Colombia - Camacho M, Rodolfo; Carvajal, Lenny Y; Castellanos Dominguez, Yeny Z; Díaz, Wilson F; Vásquez, María C (Revista Colombiana de Ciencias Pecuarias, 2015)
Background: cattle farming is an important economic activity in several regions of Colombia. However, farmers are unaware of their cattle health status, and particularly of bacterial, parasitic, and viral diseases, which affect reproduction and profitability. Objective: to assess the presence of IgG antibodies against infectious bovine rhinotracheitis (IBR), bovine viral diarrhea (BVD), bovine leukosis, leptospirosis, brucellosis, and Neospora caninum in breeding bulls in the Magdalena Medio of Colombia, according to age, breed, and origin. Methods: a descriptive, cross-sectional study was conducted with 174 male breeding cattle from severalsubspecies. Animals were above 18 months of age and belonged to dual-purpose farms in the Magdalena Medio region. Presence of IgG anti-IBR, BVD, brucellosis, neosporosis, and leukosis antibodies were determinedwith an enzyme-linked immunosorbent assay (ELISA). A sample of 156 males was assessed for leptospirosis using a microscopic agglutination test (MAT) in a dark field. Results: IgG anti-IBR antibodies were found in92.5% of the animals, anti-BVD in 62.6%, anti-Neospora caninum in 79.3%, anti-Brucella abortus in 4.02%, anti-Leptospira pomona in 8.33%, and anti-L. hardjo in 15.38%, with >1:100 titres. Besides, 64.94% prevalence was observed for bovine leukosis. Conclusions: a high prevalence of IgG anti-IBR, IgG anti-BVD, IgG anti-Neospora caninum, IgG anti-leukosis, and IgG anti-lepstospirosis antibodies were observed in Magdalena Medio bulls. With respect to B. abortus, confirmatory and competitive ELISA test should be performed and sanitary standards need to be established. Detection of IgG antibodies among bulls reveals poor sanitary conditions, absent of protective-vaccination antibodies and an urgent need for health control measurements.